Agape: un concetto per le scienze sociali - Iorio, Gennaro (SocietàMutamentoPolitica, 2012)
The aim of this paper is to place in contemporary social theory the concept of agape. It is ancient for theological research and, in some respects, philosophical, but unpublished for the social sciences, except for recent work such as Luc Boltanski. The effort to define the concept of agape, trace the epistemological boundaries, identify the size, distinguish the meanings and use it for the empirical analysis are the main points developed by the wise. In this perspective, the author suggests that the agape makes us reconsider the deepest vocation of the social sciences, namely, that in addition to the prospects of self-analysis, both reaffirmed the emancipatory character of the discipline it, and then, the prospect of critical theory.